A field investigation into penetration cracks close to dam-to-pier interfaces and numerical analysis. (November 2015) - Zhang, Qi-Ling; Wang, Fan; Gan, Xiao-Qing; Li, Bo
Abstract: This paper is a preliminary attempt to clarify a cracking issue confronting a double-curvature arch dam. The cracking occurs in the immediate vicinity of the interfaces between the dam body and some of its gate piers. This study seeks to address what is the biggest factor in the occurrence of the cracks. Both an on-site examination and a finite element analysis (FEA) were performed. The on-site examination consists of crack inspection and a concrete strength test. The FEA primarily focuses on structural loads (gravity and hydraulic thrust). The most obvious finding to emerge from the on-site examination is the symmetrical distributions of the cracks in the piers. The trends of the calculated stress contours correlate fairly well with those of the observed crack propagations, regardless of whether or not the hydraulic thrust is considered in the FEA. Our work has led us to conclude that the cracks result primarily from gravity rather than the hydraulic thrust. The cracking issue is independent of the water storage of the reservoir. Long-term and regular monitoring of the cracking lengths and openings should be a priority. The present findings have important implications for further reinforcement and maintenance work on the cracking gate piers. Highlights: The observed cracks in the left and right piers are in the main symmetrical. The stress contours and the observed crack propagations are in good agreement. The cracks result primarily from gravity rather than the hydraulic thrust. The cracking issue is independent of the water storage of the reservoir.